The role of good corporate governance in enhancing firm value: Operational efficiency as a mediating variable in financial conglomerate banking companies in Indonesia - Sigalingging, Juliser; Sumiati, Sumiati; Ratnawati, Kusuma; Indrawati, Nur Khusniyah (Edelweiss Applied Science and Technology, 2025)
This study is motivated by the inconsistent empirical findings regarding the influence of Good Corporate Governance (GCG) on firm value, particularly in financial conglomerate banking companies in Indonesia. The purpose of this study is to empirically examine the impact of GCG on firm value, with operational efficiency serving as a mediating variable. Employing a quantitative approach, this research utilizes path analysis and multiple linear regression on secondary banking data covering the period from 2015 to 2023. The findings indicate that the implementation of GCG has a positive and significant impact on firm value. Moreover, GCG significantly influences operational efficiency, which in turn mediates the relationship between GCG and firm value more strongly than the direct effect alone. The study concludes that an effective and structured implementation of GCG not only enhances internal operational efficiency but also strengthens firm value in the eyes of shareholders and investors. These findings provide important implications for policymakers and corporate management in enhancing the competitiveness of the financial sector.